A broadband metal coaxial resonator antenna loaded with dielectric lens. Issue 12 (8th September 2021) - Tan, Jing; Chen, Juan; Sang, Xiangyuan; Luo, Man
Abstract: A design method of metal coaxial resonator antenna (MCRA) is proposed in this article. According to this method, a broadband MCRA working in high‐order modes is designed. The proposed antenna fuses two frequency bands of different high‐order mode pairs, thus achieving 30% fractional bandwidth. The measured operating frequency band of the antenna is 2.95–4.1 GHz, in which the gain is more than 8.5 dBi. In addition, in order to improve the gain, a low‐profile dielectric lens (DL) is designed. With the DL loaded, the −10 dB S11 band shifts to 3.1–4.1 GHz, and the gain of is more than 11 dBi. A close agreement has been achieved between the measured and simulated results.